LENGTHENING OVER NAIL– HOW I DO IT - Tawil, Basir (International Journal of Allied Health Sciences, 2021)
Bone Lengthening using an external fixator has become a standard method to treat LLD (Limb Length Discrepancy) due various causes including congenital or acquired such in trauma or infection of the extremities. Bone Lengthening has many advantages including the unlimited amount of bone regeneration, control distraction up to the desired length and the early weight bearing. Although distraction osteogenesis provides a highly satisfactory means of gaining bone length, prolonged use of an external fixator is always a challenge for patients and complications are almost inevitable, such as pin-tract infections, deep infection, and joint contractures. To reduce the period of external fixation, hybrid Bone Lengthening techniques has been developed. Bone Lengthening over the nail (BLON) reduces external fixation times because the fixator can be removed while the distraction callus is consolidating. However, there is a risk of developing deep infection leading to failure of the treatment, which could result from the close contact between the nail and the pins and wires. The positioning of the external fixator pins or wires around an IM nail at the diaphysis is difficult, given the limited space available. This short presentation will share how to perform BLON for such cases.